Bone Mineral Density Responses to Obesity Reduction with Enhanced Protein: Short Term Results in Functionally Frail Older Adults (OR18-04-19). (13th June 2019) - Starr, Kathryn Porter; Lyles, Kenneth; Miller, Marshall; Rincker, Jamie; McDonald, Shelley; Patel, Dipa; Pieper, Carl; Bales, Connie
Abstract: Objectives: With soaring rates of geriatric obesity, a major shift in understanding of the relationship between body mass and bone health is unfolding. The premise that obesity is protective of bone runs counter to evidence that obesity factors like increased inflammation and reduced physical activity may increase fracture risk. Methods: Obese (BMI ≥ 30 kg/m 2 ) older (≥60 yrs) participants (female n = 42; male n = 12; 46% Black) with functional limitations (mean Short Physical Performance Battery score = 9.2 ± 1.4 out of 12) were randomized to an RDA level protein weight loss regimen (0.8 g/kg bw/d; Control; n = 25) or a higher protein arm (1.2 g/kg bw/d, with ≥30 g high quality protein [predominantly dairy] at each meal; Protein; n = 29). Both groups followed a hypo-caloric diet and participated in supervised low-intensity chair exercises, (three 30 min sessions/wk). Measurements at baseline and 6 months included body weight, body fat (BodPod), and bone mineral density (BMD by Dual X-ray Absorptiometry) lumbar spine (LS), total hip (TH) and femoral neck (FN) and bone condition classified as normal, osteopenia, or osteoporosis. Results: Mean baseline characteristics were BMI 34.3 ± 4.7 kg/m2 and age = 70.0 ± 6.1 yrs; 42 had normal BMD, 18 osteopenia and 4 osteoporosis. Compared to baseline, weight loss and body fat reduction were significant ( P < 0.001) at 6 months in both Control (7.7%) and Protein (6.4%) with no group difference. Between 0 and 6 months, BMD was unchanged for TH or FN in either group but increased for LS (0.164 ± 0.293 g/cm 2 ; P < 0.01) in Protein. BMD at LS was unchanged in Control (0.0111 ± 0.0497 g/cm 2 ; P = 0.295) but there was no group difference in LS change. The number of participants with osteoporosis was unchanged at 6 months. Conclusions: Study findings show no detrimental changes in bone health following a 6-month obesity intervention; this was the case for both groups and could result in part from the regular physical exercise during weight loss. Conclusions must take into account the interim nature of these preliminary findings, since bone turnover responses to a physiologic challenge can take a year or more to fully equilibrate. Long-term study of the influence of this obesity intervention on BMD is warranted. Funding Sources: National Dairy Council and US Department of Veterans Affairs Rehabilitation Research and Development Service Program (CDA-2/IK2 RX002348).